Early Warning and "Ethnic" Conflict Management: Rwanda and Kosovo - Adelman, Howard (Refuge: Canada's Journal on Refugees, 1999)
The author examines the way in whichpast conflicts shape the responses to currentcrises. In examining the facts of theRwandan case compared with what isknown of the Kosovo crisis, he identifiesa number of similarities shared in bothcontexts. However, these first order similaritiesprove to be outweighed by thedifferences in the capacity for controlpossessed by Milosevic, the ethnic anddemographic composition of the communitiesin the conflict, and military capabilities.Importantly, levels of publicsupport for action were higher in the caseof Kosovo, as were the steps taken by theinternational community in the leadupto the bombing.